Introduction to sustainable infrastructure engineering design - Neumann, Edward S. (Hoboken : Pearson, 2016)
'Civil engineering is a profession that has a distinct focus on the design of infrastructure systems. There are major differences between the characteristics of the infrastructure design problems that civil engineers solve and the problems examined by other engineering disciplines, which tend to emphasize the design of smaller items produced for short term use. Beginning students in civil engineering should be made aware of these distinctions and the types of systems civil engineers design so that they can begin to think about the problems associated with them. This is the starting point for evolving into professional civil engineers whose area of expertise is design of the civil works infrastructure that supports modern societies.'--
Civil engineering infrastructure systems -- Sustainability and design -- Climate change -- Federal laws and acts -- The phases of design -- Needs assessment and problem definition : Report 1 -- Establishment of design goals : Report 2 -- Synthesis and the generation of alternatives : Report 3 -- The evaluation of alternative solutions : Report 3 -- Development of site maps and data bases -- Site evaluation and use of contour lines -- Abstraction and modeling -- Licensure, ethics, liability -- Team management, communications, and leadership -- Undergraduate and graduate curricula and programs.
Includes index and references.
Keywords: Sustainable engineering -- Textbooks; Civil engineering -- Textbooks; Sustainable design -- Textbooks; Sustainable construction -- Textbooks